Textos de divulgação científica e as histórias em quadrinhos: um estudo das interpretações de estudantes do ensino médio - Fioresi, Claudia Almeida (2016)
One of the media's functions is to communicate science constituting a discursive genre that we call dissemination of science communication. Also the Comics are considered a specific genre of discourse, which can be used as a teaching resource for science classes. This work was carried out by a production activity of comics, which aimed to grant the dissemination of science. The production of comic books was performed by high school students from a public school in the city of Toledo/PR, in order to investigate how these students divulge certain issues of Science. Initially, it was performed the analysis of two texts "Paradise Pesticides", the journal Science Today and "The Truth About Gluten," the Journal Superinteressante. Our intention was to make a critical reading and to find out how each issue was addressed by their authors. It was verified the presence or non-objectivity of indices and some didatizantes elements. Based on the analysis, we observed that the text relating to gluten has a greater amount of didatizantes elements which seek a closer relationship with the reader, but can lead to erroneous relations of science. The text of pesticides have fewer didatizantes elements, which makes it closer to science. These two texts were brought to the classroom for reading and discussion with students, who could then, build their own comics. Later, it was worked the analysis of Comics produced by the students, which was held based on the method of content analysis, following the premises of Bardin (2011). The speeches found in Science dissemination of texts provided to students reflected directly in the content of elaborate stories in which can be seen an uncritical reading of the text by students, representing reductive perceptions of Science and Technology. Finally, considerations can anticipate that it is important to conduct critical anaylisis of the dissemination of science texts in the classroom then students can develop a critical look at the reports in the media.